Ginsenosides: Allies of gastrointestinal tumor immunotherapy - Yutao Feng; Fen Ma; Enjiang Wu; Zewei Cheng; Zhengtao Wang; Li Yang; Jiwei Zhang (Frontiers Media S.A., 2022)
In the past decade, immunotherapy has been the most promising treatment for gastrointestinal tumors. But the low response rate and drug resistance remain major concerns. It is therefore imperative to develop adjuvant therapies to increase the effectiveness of immunotherapy and prevent drug resistance. Ginseng has been used in Traditional Chinese medicine as a natural immune booster for thousands of years. The active components of ginseng, ginsenosides, have played an essential role in tumor treatment for decades and are candidates for anti-tumor adjuvant therapy. They are hypothesized to cooperate with immunotherapy drugs to improve the curative effect and reduce tumor resistance and adverse reactions. This review summarizes the research into the use of ginsenosides in immunotherapy of gastrointestinal tumors and discusses potential future applications.